Optimization of Fast Moving Consumer Goods (FMCG) marketing channels in China: a case study - Chun, Chen (2016)
The operation conditions of marketing channels, regarded as the crucial external resources of enterprises, directly influence the market position of a company. Good marketing channels are significant links for enterprises to perceive market change and adjust enterprise behavior and decisions. This thesis seeks to clarify and define various factors influencing marketing channels optimization by using fast moving consuming goods (FMCG) as the focus of the research topic and by taking Rainbow Company as an example, based on data of an actual marketing channel operation and deep research on the case company. On this basis, the concept and basic framework of marketing channel optimization of FMCG enterprises has been considered from the perspective of channel relationship selection and marketing channel integration, considering the influence of direct online marketing models on traditional marketing channels. Finally, it has put forward the implementation strategy of marketing channel optimization from three aspects, building strategic alliance of marketing channels, putting more effort in developing a network channel and in strengthening regional marketing team construction by applying relevant theories and concepts of marketing channel optimization.